KERANGKA PEMANFAATAN CLOUD COMPUTING DI PEMERINTAH DAERAH - , Ronggo Radityo Nimoko, Dr. Ir. Lukito Edi Nugroho, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Local governments began to take advantage of Information and Communications Technology (ICT) intensively in accordance with the instructions of President of the Republic of Indonesia Number 3 of 2003, but sometimes constrained by budget and time for procurement. It took lengthy process for ICT infrastructure equipment procurement while in the mean time the already existing ICT infrastructures has not been fully utilized. Cloud computing was promoted to be able to consolidate the ICT infrastructure, simplify management, maximize the utilization of computing resources and ultimately saving the operational costs of ICT. îis research aims to study the utilization of cloud computing suitable to be applied in local governments and designing the cloud computing framework for local governments.